Democracy's resilience to populism's threat countering global alarmism - Weyland, Kurt 1958- (Cambridge University Press, 2024)
"This book demonstrates that populism's threat to democracy is less severe than often feared. The comprehensive, systematic analysis of contemporary Latin America and Europe over the last four decades and of the U.S. under Trump shows that populist chief executives destroy democracy only under special, restrictive conditions"--